Supply of affordable high quality potato seed for potato production in the Red River Delta of Vietnam - Dang, Thi Hue (Curtin University, 2008)
Poor quality seed is the major constraint limiting both the productivity of potato crops and the expansion of the potato industry in Vietnam. Despite numerous attempts to establish a certified seed system, the most practical solution is to import clean foundation seed of the desired variety and physiological age. With imports from Europe and North America proving to be immature and too expensive, Western Australia (WA) has emerged as a potential source of high quality seed. While seed imports from WA are unique in that the varieties imported have been selected by researchers in Vietnam as being suited to the agro-ecological environment in the Red River Delta (RRD), no assessment of the economic benefits to smallholder potato farmers from the use of WA potato seed has been undertaken. In 2006/08, the yield and profitability of three potato varieties Eben, KT3 and Atlantic in two locations were compared where the crops had been derived from new seed imported from WA (VN0), seed derived from crops cultivated in the RRD after one generation (VN1) and two generations (VN2). There was a significant difference in the yield produced between the three different seed sources but not between the locations. For all varieties, and in both years, the yield decreased with the number of multiplications in Vietnam. Furthermore, the marketable yield declined significantly from the first crop (VN0) to the third crop (VN2). The decline in yield and tuber quality with each successive generation was associated with an increase in PVY and PVX infection. Not unexpectedly, differences in yield and marketable yield between the seed generations had a significant impact on the gross income for each variety.VN0 seed of all varieties produced the highest gross income (VND 2.4 to 4.1 M/sao) compared to VN1 (VND 1.9 to 3.1 M/sao) which was significantly higher than VN2 (VND 1.4 to 2.4 M/sao). However, while high quality seed is more productive, it is also more expensive. As a result, significant differences were observed between the seed costs. VN0 seed was almost two times more expensive (VND 10,500 – 11,000 per kg) than VN1 and VN2 seed (VND 6,000 – 6,500 per kg). Despite the higher costs, VN0 seed provided the highest net incomes compared to VN1 which was significantly higher than VN2. Farmers who retained seed received a higher net income (VND 0.13 – 0.6 M/sao) than those who did not retain seed. Ways to improve the accessibility of affordable, high quality potato seed to farmers in the RRD are discussed.